The Impact of Training on Medication Error Rate of the Emergency Department in Hospitals Affiliated to Golestan University of Medical Sciences - Hajibeglou, Azam; Zagheri Tafreshi, Mansoureh; Kamrani, Farhad; Nasiri, Malihe (Advances in Nursing & Midwifery, 2018)
Abstract Introduction: Medication errors are the most common type of medical errors that can cause serious problems for public health and are considered a threat to patient safety. This study was conducted to determine the effectiveness of patient safety training on nurses’ medication errors at the emergency department of a hospital of Golestan Province in Iran. Methods: The present quasi-experimental study was conducted from March to September 2016. The study population consisted of nurses working at a hospital affiliated to Golestan University of Medical Sciences and a sample of 40 nurses at the emergency department of this hospital were selected through a census. The data collection tools used included a demographic questionnaire and Wakefield’s Medication Error questionnaire for nurses (consisting of 21 domains), which were used once their reliability was confirmed. A patient safety training program was designed and implemented for the selected emergency nurses in the form of a twoday workshop. The obtained data were analyzed using the SPSS-18 software with the Wilcoxon test. Results: Results showed that the rate of medication errors (80.62%) of nurses were at a low level. The majority of nurses (80.62%) scored low in terms of the frequency of medication errors; after the training, a significantly greater number of nurses scored low in terms of this index (90.31%; P < 0.001). The analyses showed the effectiveness of the patient safety training program for nurses in the two domains of wrong time error and missed dose error (P < 0.001); however, the training had no significant effects in the other domains. Conclusions: As patient safety training can be effective on nurses’ medication errors, retraining courses on safe medication administration are necessary regarding nurses’ significant role in the prevention of medication errors.